A distinctive new species of Protozantaena Perkins, 1997 from lowland Namaqualand, South Africa (Coleoptera, Hydraenidae) - Bilton, David T.; Mlambo, Musa C. (Zootaxa, 2024)
Protozantaena gigantea sp. nov. is described, based on specimens collected from residual pools in a drying seasonal river in Namaqualand, Northern Cape Province, South Africa. Morphologically, the new species appears to be related to P. labrata Perkins, 1997 from Namibia and P. birdi Bilton, 2022, from the Great Escarpment in the Eastern Cape Province. At up to 2.0 mm in body length, the new species, whilst small, is by far the largest African Protozantaena Perkins, 1997 known to date. The opportunity is also taken to report a new record for P. birdi in the Eastern Cape Drakensberg.